How do compulsory citizenship behaviors affect moral disengagement in organizations? Significance of anger toward the organization during the COVID-19 pandemic - Yildiz, Bora; Yildiz, Harun; Ozbilgin, Mustafa (Frontiers in Psychology, 2022)
Background: With the COVID-19 pandemic, healthcare professionals, especially nurses, are confronted with an intensified workload. The literature on compulsory citizenship behaviors and their consequences is still far from explaining the cognitive and emotional mechanisms that underlie this relationship. Methods: Drawing on the resource depletion theory, this paper aims to unpack the mechanism by which compulsory citizenship behaviors influence moral disengagement with the mediation effects of anger towards the organization. Drawing on a cross-sectional survey of nurses (n = 294) in private and public hospitals in Turkey, the data analysis was based on a structural equation model and Bayesian mediation analysis. Result: The study revealed that compulsory citizenship behaviors positively influenced anger toward the organization and moral disengagement. Further, anger toward the organization positively and fully mediates the link between compulsory citizenship behaviors and moral disengagement. Likewise, the Bayesian mediation analysis indicated that the proportion mediated (PM), which ensures a prediction of the extent to which the pathway explains the total effect through the mediation effect, was 33.74%. Conclusion: The findings show that exposure to compulsory citizenship behaviors leads to negative emotional (anger towards to organization) and cognitive (moral disengagement) consequences in nurses. Practical implications: Hospital managers should not force nurses to display discretionary work tasks outside their job descriptions. Providing an organizational milieu where voluntarily extra-role behaviors are encouraged may help reduce nurses’ moral disengagement and, in turn, ease their anger toward the organization.